Comparison of novel markers of metabolic complications and cardiovascular risk factors between obese non-diabetic and obese type 1 diabetic children and young adults - Kącka, Anna; Charemska, Anna; Jarocka-Cyrta, Elżbieta; Głowińska-Olszewska, Barbara (Frontiers in Endocrinology, 2022)
Objectives: For the past years the prevalence of obesity is growing in general population of children, but also among diabetic patients, resulting in increased risk of cardiovascular complications. Type 1 diabetes mellitus (T1DM) is one of the most common chronic diseases in children and young adults, leading to decreased life quality and lifespan, with obesity being recognised recently as a major contributing factor to these health problems. The objective of this study was to analyse and compare the selected novel markers for metabolic complications of the obesity and vascular risk factors between obese non-diabetic and obese T1DM children and young adults. Methods: 104 subjects, aged between 10-24 years,31 with T1DM and excessive body weight, 41 with obesity without diabetes, 32 with T1DM and normal weight, and 32 matched lean controls were included into the study. Clinical characteristics, blood pressure measurements, daily requirement for the insulin, HbA1c%, plasma lipids, fetuin-A, E-selectin and osteoprotegerin levels, were compared with respect to body mass index (BMI), body mass index standard deviation score (BMI-SDS) and intima media thickness (cIMT) of common carotid arteries. Results: Patients with T1DM and excessive body weight compared to non-diabetic obese subjects had similar values of systolic blood pressure (125.6±8.2 vs. 127.3±12.9 mmHg, p=0.515), diastolic blood pressure (78.19±7.03 vs. 78.02±8.01 mmHg, p=0.918), cholesterol (175.26 ± 34.1 vs. 163.51±26.08 mg/dl, p=0.102),LDL(108.03±32.55 vs. 112.22±26.36 mg/dl, p=0.548). Triglyceride levels (118.19±71.20 vs. 117±55.80 mg/dl, p=0.937), all values were found to be higher compared to non-obese T1DM and healthy controls. HbA1c level, and insulin resistance indices were significantly worse in T1DM obese vs T1DM non-obese patients. Fetuin A levels were higher among obese non-diabetic patient (p=0.01), E-selectin and osteoprotegerin levels were similar in both groups with obesity, but higher than in the reference group. There were no statistical differences in cIMT with T1DM with normal weight, excessive weight, and with non-diabetic obese children, however cIMT value was higher compared to reference group. Conclusion: Novel markers of metabolic complications of obesity are similar between obese T1DM vs non-diabetic subjects. Obesity in patients with T1DM results in worse metabolic control, insulin resistance and increased risk for vascular complications.